Optimal smart gateway deployment for the Internet of Things in smart home environments - Po-Chiang Lin (2015 IEEE 4th Global Conference on Consumer Electronics (GCCE), 2015)
For the Internet of Things In smart home environments, the smart gateway is the key component to collect/disseminate information from/to various sensors/actuators. In this study we investigate the smart gateway deployment problem in smart home environments. This problem is formulated as a constrained optimization problem with the objective to minimize the deployment cost subject to the constraints that all service areas should be covered. The smart gateway deployment problem under consideration is formulated as a binary integer programming problem. We solve it by the branch and bound method which could effectively reduce the complexity.